Report of a curricular internship in a CRO: regulatory affairs and pharmacovigilance study coordination - Brito, Ana Raquel Neves (2022)
This report was elaborated as part of the Master in Clinical Research Management, held between October 2020 and April 2021.This report begins by fitting the field of regulatory affairs and pharmacovigilance into the context of clinical research, as well as to detail the activities undertaken during the curricular internship at BlueClinical. During the period of training, it was possible to perform tasks inherent to the different activities undertaken by Regulatory Affairs and Pharmacovigilance team. Besides this, there was also the opportunity to perform activities related to the position of Clinical Studies Coordinator at the Centro Hospitalar do Baixo Vouga. All above allowed the acquisition of practical knowledge regarding the field of Clinical Research in Portugal.